A COMPARATIVE STUDY OF MORPHO-ANATOMY, THE CONTENT OF CHLOROPHYLL AND ASCORBIC ACID ON ARDISIA HUMILIS THUNBERG IN THE AREA WITH DIFFERENT LIGHT INTENSITY AT THE NATURE PRESERVE OF PANANJUNG PANGANDARAN, WEST JAVA, INDONESIA - Lestari, Anandira Witri; Setiawati, Tia (MATTER: International Journal of Science and Technology, 2018)
This study was conducted in order to seek out different morpho-anatomy responses, the content of chlorophyll and ascorbic acid in Ardisia humilis Thunberg in the area of different light intensity in the nature preserve of Pangandaran. The determination of the location was based on the existence of Ardisia humilis Thunberg in the area both with direct exposure of sun light and not. The location to obtain the open area-sample was located behind the office of Conservation of Natural Resources (BKSDA) with the light intensity of 922.000 Lux. The light intensity of the area without direct sun light exposure was 7906.6 Lux and the location was in Ciborok. Three leaves of three different plants were obtained as the samples. The observed parameter was the width and thickness of the leaves, the density of stomatal, the thickness of palisade, the content of chlorophyll and ascorbic acid. Ascorbic acid test used the method of iodometric titration. The result of the study showed that the average of the leaf thickness, leaf area, stomatal density, palisade thickness, chlorophyll content, and ascorbic acid on sun leaves were 0.25 mm, 46.032 cm2, 132.48 cells/mm2, 54.89 µm, 10.88 CCI, and 0.0077 mg/g, respectively; while, for shade leaves were 0.23 mm, 57.159 cm2, 116.63 cells/mm2, 47.66 µm, 32.41 CCI, and 0.0107 mg/g, respectively. In the sun area, it has higher average of leaf thickness, lower level of surface, higher level of stomata density and palisade thickness, and lower average of chlorophyll and ascorbic acid content compared to the one in the shade area.